Intercultural Communication Patterns in Bugis–Lauje Marriages: Negotiating Identity and Harmony in Rural Central Sulawesi, Indonesia - Kaddi, Sitti Murni; Fadhliah, Fadhliah; Badollahi, Muh. Zainuddin; Utama, Roman Rezki (Journal of Contemporary Rituals and Traditions, 2025)
Purpose: This study aims to analyze the intercultural communication patterns between Bugis–Lauje couples in Tinombo, Central Sulawesi. The research aims to understand how these couples navigate linguistic, emotional, and cultural differences in their daily lives, and how traditional rituals and family mediators serve as bridges of meaning to maintain marital harmony. Methodology: The research employs a qualitative case study approach with six purposively selected informants, including two interethnic couples, two family members, and two traditional leaders. Data were collected through semi-structured interviews, participatory observation, focus group discussions, and document analysis, then analyzed using the Miles and Huberman interactive model with triangulation and member checking to ensure validity. Findings: The findings show that Bugis–Lauje couples achieve intercultural harmony through continuous negotiation and adaptation. Indonesian functions as a neutral lingua franca in household communication, while Bugis and Lauje languages are used in rituals to maintain cultural identity. Couples adopt adaptive strategies such as humor, patience, code-switching, and family mediation to transform potential misunderstandings into mutual understanding. Rituals like mappacci (Bugis) and modutu (Lauje) serve as symbolic spaces of cultural dialogue, reinforcing kinship ties and social cohesion. Implications: The study makes significant contributions both theoretically and practically. Theoretically, it extends Kim’s Stress–Adaptation–Growth model, Giles’s Communication Accommodation Theory, and Ting-Toomey’s Face-Negotiation Theory within the Indonesian intercultural context. Practically, it proposes policy recommendations such as pre-marital intercultural communication modules at KUA, handbooks for family mediators, and bilingual ritual literacy programs to enhance cross-ethnic understanding in rural communities. Originality and Value: This research makes a novel contribution by focusing on the domestic sphere of intercultural communication in rural Central Sulawesi—an area that has been rarely examined in prior studies. It introduces the concept of a hybrid communication model that merges linguistic, cultural, and emotional elements, illustrating how multiethnic families act as agents of social cohesion in Indonesia’s multicultural landscape.